2019
DOI: 10.1038/s41598-019-41285-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of live attenuated Enterovirus 71 vaccine strains that confer protection against lethal challenge in mice

Abstract: Besides causing mild hand, foot and mouth infections, Enterovirus A71 (EV-A71) is associated with neurological complications and fatality. With concerns about rising EV-A71 virulence, there is an urgency for more effective vaccines. The live attenuated vaccine (LAV) is a more valuable vaccine as it can elicit both humoral and cellular immune responses. A miRNA-based vaccine strain (pIY) carrying let-7a and miR-124a target genes in the EV-A71 genome which has a partial deletion in the 5′NTR (∆11 bp) and G64R mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Notably, similar effects were obtained in mice rendered genetically unresponsive to IFN, which nevertheless generated protective antibodies against reinfection by between 10 and 10 000 times the LD 50 of wild‐type PV . This approach was recently used by Yee et al . towards developing a live attenuated vaccine for enterovirus 71.…”
Section: Challenges and Strategies In Targeting Multifunctional Hostsupporting
confidence: 85%
“…Notably, similar effects were obtained in mice rendered genetically unresponsive to IFN, which nevertheless generated protective antibodies against reinfection by between 10 and 10 000 times the LD 50 of wild‐type PV . This approach was recently used by Yee et al . towards developing a live attenuated vaccine for enterovirus 71.…”
Section: Challenges and Strategies In Targeting Multifunctional Hostsupporting
confidence: 85%
“…Another study also indicated that EV-A71 with the RdRp-G64R and RdRp-L123F mutations attenuated the virulence of the virus in an AG129 mouse model [108]. Yee et al [109] constructed an miRNA-based EV-A71 vaccine strain, pIY, which carried let-7a and miR-124a target genes. They found that the viral yield of the pIY strain was much lower than that of the EV-A71 wild-type B4 strain 41 in SHY-5Y cells.…”
Section: Development Of An Ev-a71 Vaccinementioning
confidence: 99%
“…34,35 High levels of neutralizing antibody (NtAb) titres, together with IFN-γ secretion following vaccination, were able to confer 100% protection against hind limb paralysis from EV-A71 challenge, suggesting that humoral immune response might be able to protect mice from being killed by high viral load. 36…”
Section: B and T Cell Immunity Against Ev-a71mentioning
confidence: 99%
“…44 In fact, there are a few successful LAVs that are used today, such as the attenuated yellow fever vaccine, influenza vaccine, chickenpox vaccine and the measles, mumps, and rubella vaccines. Recently, two LAVs against EV-A71 were constructed by Yee and colleagues; 36 one is a multiply mutated strain (MMS) and the other, the pIY strain, carried two additional micro-RNAs (Let 7a and MicroRNA 124) in the EV-A71 genome, which carried a deletion in the 5′NTR and a G64R mutation. This study demonstrated that both MMS and pIY strains were genetically stable after 20 serial passes in vitro .…”
Section: Development Of Monovalent Vaccines Against Ev-a71mentioning
confidence: 99%
See 1 more Smart Citation